2000
DOI: 10.1007/s004250000308
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glutathione synthesis reduces chilling tolerance in maize

Abstract: The role of glutathione (GSH) in protecting plants from chilling injury was analyzed in seedlings of a chilling-tolerant maize (Zea mays L.) genotype using buthionine sulfoximine (BSO), a specific inhibitor of gamma-glutamylcysteine (gammaEC) synthetase, the first enzyme of GSH synthesis. At 25 degrees C, 1 mM BSO significantly increased cysteine and reduced GSH content and GSH reductase (GR: EC 1.6.4.2) activity, but interestingly affected neither fresh weight nor dry weight nor relative injury. Application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 47 publications
5
36
0
Order By: Relevance
“…Strong evidence for a relationship between tissue glutathione and chilling tolerance in maize has come from several studies by Kocsy and co-workers. In particular, these authors have shown that chilling tolerance is accompanied by increased g-ECS activity and GSH accumulation (Kocsy et al, 1996(Kocsy et al, , 2000a(Kocsy et al, , 2000b(Kocsy et al, , 2001b. Hence, we cloned maize genes encoding g-ECS and GSH-S.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong evidence for a relationship between tissue glutathione and chilling tolerance in maize has come from several studies by Kocsy and co-workers. In particular, these authors have shown that chilling tolerance is accompanied by increased g-ECS activity and GSH accumulation (Kocsy et al, 1996(Kocsy et al, , 2000a(Kocsy et al, , 2000b(Kocsy et al, , 2001b. Hence, we cloned maize genes encoding g-ECS and GSH-S.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf glutathione contents correlate with chilling resistance in maize (Kocsy et al, 1996(Kocsy et al, , 2000a(Kocsy et al, , 2000b(Kocsy et al, , 2001a(Kocsy et al, , 2001b. Furthermore, our previous data suggest that one factor in the sensitivity of maize to both shortterm and long-term chilling may be restrictions over glutathione reduction and cycling between cell types (Doulis et al, 1997;Pastori et al, 2000a).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Several transgenic plants with elevated levels of GSH have been shown to be resistant to oxidative stress (Foyer et al, 1995;Wellburn et al, 1998). In addition, elevated GSH synthesis by increasing g-glutamyl-Cys synthetase activity was shown to correlate with cadmium resistance in cultured tomato (Solanum lycopersicum) cells (Chen and Goldsbrough, 1994) and chilling tolerance (Kocsy et al, 2000(Kocsy et al, , 2001. During the growing stage, an exogenous supply of GSH alone at 400 mM had an obvious effect of enhancing the drought tolerance of wild-type plants.…”
Section: The Roles Of Gsh and Aba In Enhancing Drought And Salt Tolermentioning
confidence: 99%
“…GR activity was measured according to Kocsy et al (2000) with slight modifications. Absorbance was taken at 412nm for 3m (extinction coefficient 6.2mM -1 cm -1 ).…”
Section: Glutathione Reductase Activitymentioning
confidence: 99%